Mollusks of Candomblé: symbolic and ritualistic importance - Léo Neto Nivaldo A; Voeks Robert A; Dias Thelma LP; Alves Rômulo RN (BMC, 2012)
Abstract Human societies utilize mollusks for myriad material and spiritual ends. An example of their use in a religious context is found in Brazil's African-derived belief systems. Candomblé, an Afro-Brazilian religion introduced during the 18th-19th centuries by enslaved Yoruba, includes various magical and liturgical uses of mollusks. This work inventoried the species utilized by adherents and to analyzed their symbolic and magical context. Data were obtained from Candomblé temples in two cities in the northeast of Brazil-Caruaru, in the state of Pernambuco, and Campina Grande, in the state of Paraíba. Questionnaires administered to eleven adepts revealed that at least nineteen mollusk species are being used. Shells from Monetaria moneta, M. annulus and Erosaria caputserpentis were cited by all of the interviewees. Three uses stood out: divination (jogo de búzios); utilization as ritual objects; and employment as sacrificial offerings (Igbin or Boi-de-Oxalá). The jogo de búzios (shell toss), employed in West Africa, Brazil and Cuba, is of fundamental importance to the cult, representing the means by which the faithful enter in contact with the divinities (Orixás) and consult people's futures (Odu). The utilization of mollusks in Candomblé is strongly influenced by ancient Yoruba myths (Itãs) which, having survived enslavement and generations of captive labor, continue to guide the lives of Brazil's African Diaspora.